Coping Behavior Of Melinda In Speak Novel By Laurie Halse Anderson (1999): An Individual Psychological Approach - Kristiana, Kristiana (2012)
The major problem of this study is to reveal the coping behavior of Melinda Sordino reflected in Laurie Halse Anderson's Speak novel. The objectives of the study are to analyze Laurie Halse Anderson's Speak novel based on the structural elements of the novel and to analyze the character of Melinda Sordino based on individual psychological analysis developed by Alfred Adler. This study belongs to qualitative study. In this method, there are two types of data sources, which are used to do the research, namely primary data and secondary data sources. The primary data source is Speak novel by Laurie Halse Anderson, meanwhile the secondary data source are taken from other resources related to the analysis such as internet, books, and other references which are related to this study. In analyzing the data, she applies two approaches. Firstly, structural approach is used to analyze the elements of the novel. It consists of the characterization, setting, point of view, plot, style, and theme. Secondly, the individual psychological approach is used to analyze the coping behavior of Melinda Sordino in facing her life problems that influences her personality. Based on structural analysis, Anderson creates the main character - Melinda as a way to convey her idea about adolescence's coping behavior. Lauri Halse Anderson's Speak wants to convey a moral message "speaking up for yourself and others. You have to speak up for what you believe in or nothing will ever change. Melinda that success to get much impression for a Novel; continually plot from the beginning, the middle and the end; the point of view have been done in all ways precisely appropriate applied in the most setting place; and the other elements have the unity and successful relate to one another then finally formulated into good quality of a novel. Based on individual psychological approach the writer finds that the character of Melinda Sordino gets maturity in her personality that is shaped from her effort to cope her problems in gaining her life goals. She gets her strength and she can express her pain and emotion through the Tree Art Work.